2022
DOI: 10.3389/fnut.2022.1041026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an exogenous ketone ester using multi-omics in skeletal muscle of aging C57BL/6J male mice

Abstract: Exogenous ketone ester supplementation provides a means to increase circulating ketone concentrations without the dietary challenges imposed by ketogenic diets. Our group has shown that oral R,S-1,3, butanediol diacetoacetate (BD-AcAc2) consumption results in body weight loss or maintenance with moderate increases in circulating ketones. We have previously shown a diet consisting of 25% BD-AcAc2 can maintain lean body mass (LBM) and induce fat mass (FM) loss in young, healthy male mice, but the underlying mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Another fascinating observation that will require additional work is that most of the weight gain in the KE-fed mice was due to a non-statistically significant increase in LBM. A recent publication from our laboratory showed that in older mice, several markers of skeletal muscle hypertrophy and atrophy are altered by BD-AcAc 2 in a pattern suggestive of improvements in skeletal muscle quantity and quality ( Roberts et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another fascinating observation that will require additional work is that most of the weight gain in the KE-fed mice was due to a non-statistically significant increase in LBM. A recent publication from our laboratory showed that in older mice, several markers of skeletal muscle hypertrophy and atrophy are altered by BD-AcAc 2 in a pattern suggestive of improvements in skeletal muscle quantity and quality ( Roberts et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional work has demonstrated that a ketogenic diet may also increase skeletal muscle mitochondrial volume ( Parry et al, 2018 ), and mitochondrial enzymatic activity ( Zhou et al, 2021 ), in preclinical models of aging. Direct ketone administration via exogenous ketone diester administration in a preclinical model also improved skeletal muscle regeneration, electron transport chain, and insulin sensitivity ( Roberts et al, 2022 ), suggesting a potential role for ketones in facilitating these changes ( Poff et al, 2020 ). Miller et al (2020) found that after 12 weeks of a LCHF/ketogenic versus a HCLF diet (both combined with a resistance exercise program), diet did not increase mitochondrial volume.…”
Section: Low-carbohydrate High-fat Diets and The Crossover Pointmentioning
confidence: 99%
“…Interestingly, the greater reductions in mean blood glucose concentrations (14.9 mg/dL) in our study ( Prins et al, 2023a ) compared to those achieved in a recently reported randomized controlled trial (7.0 mg/dL) ( Dorans et al, 2022 ), may reflect the greater restriction in carbohydrate consumption in our study (40.9 g carbohydrates/day) compared to those in the study of Dorans et al (96 g carbohydrates/day). When considering the known link between mitochondria and insulin function ( Kim et al, 2008 ; Pagel-Langenickel et al, 2010 ), and the demonstration that LCHF/ketogenic diets improve insulin sensitivity, and mitochondrial molecular signaling and function ( Newman et al, 2017 ; Parry et al, 2018 ; Miller et al, 2020 ; Huang et al, 2021 ; Zhou et al, 2021 ; Roberts et al, 2022 ), the established reductions in the blood insulin concentration when switching from a HCLF to a LCHF diet, may explain how these relatively rapid changes between diet, insulin, glucose homeostasis, and fat oxidation might be linked.…”
Section: Glucose Homeostasis In Athletesmentioning
confidence: 99%